A single base deletion in the SLC45A2 gene in a Bullmastiff with oculocutaneous albinism. (24th July 2017) - Caduff, M.; Bauer, A.; Jagannathan, V.; Leeb, T.
Summary: Oculocutaneous albinism type 4 (OCA4) in humans and similar phenotypes in many animal species are caused by variants in the SLC45A2 gene, encoding a putative sugar transporter. In dog, two independent SLC45A2 variants are known that cause oculocutaneous albinism in Doberman Pinschers and several small dog breeds respectively. For the present study, we investigated a Bullmastiff with oculocutaneous albinism. The affected dog was highly inbred and resulted from the mating of a sire to its own grandmother. We obtained whole genome sequence data from the affected dog and searched specifically for variants in candidate genes known to cause albinism. We detected a single base deletion in exon 6 of the SLC45A2 gene (NM_001037947.1:c.1287delC) that has not been reported thus far. This deletion is predicted to result in an early premature stop codon. It was confirmed by Sanger sequencing and perfectly co‐segregated with the phenotype in the available family members. We genotyped 174 unrelated dogs from diverse breeds, all of which were homozygous wildtype. We therefore suggest that SLC45A2: c.1287delC causes the observed oculocutaneous albinism in the affected Bullmastiff.